The abstract domain of Trapezoid Step Functions. (October 2015) - Cortesi, Agostino; Costantini, Giulia; Ferrara, Pietro
Abstract: The Trapezoid Step Functions (TSF ) domain is introduced in order to approximate continuous functions by a finite sequence of trapezoids, adopting linear functions to abstract the upper and the lower bounds of a continuous variable in each time slot. The lattice structure ofTSF is studied, showing how to build and compute a sound abstraction of a given continuous function. Experimental results underline the effectiveness of the approach in terms of both precision and efficiency with respect to the domain of Interval Valued Step Functions (IVSF ). Abstract : Highlights: The domain of Trapezoid Step Functions is introduced for the static analysis on continuous functions׳ values. The domain is a (proper) refinement of the Interval Valued Step Function Domain. A constructive abstraction procedure is provided that deals with floating point precision issues.